Essays on empirical macroeconomics - Aaron Mehrotra (Bank of Finland, 2006)
This thesis consists of four essays in empirical macroeconomics. The first three essays examine the conduct of monetary policy during a disinflationary and deflationary era, with the policy interest rates close to or at the zero bound.The questions of interest include the potency of the interest rate channel, the stability of broad money demand, and the possibility to use the exchange rate channel in order to affect economic activity and the price level.We use time series econometrics techniques, mainly vector autoregressions, focusing on Japan.While we find that basic relationships between the variables appear unaltered by deflation, a further stimulative impact is difficult to implement once the zero bound is hit.This can be due to political reasons, as in the case of introducing a tax on currency in order to bring about negative interest rates, or because the needed stimulus is very big, as in the case of yen depreciation to increase the price level.The last essay focuses on the fiscal policy aspects of the European Union's most recent enlargement.We examine whether the fiscal austerity required by the Maastricht criteria and the Stability and Growth Pact would be harmful for the socio-economic development of the new Member States.Introducing an indicator for socio-economic development and utilizing instrumental variables regressions, we find that fiscal retrenchment, including a lower level of public debt, would be advantageous for development.A policy implication is to maintain the Stability and Growth Pact or an equivalent intergovernmental fiscal rule to curb public spending and debt.
URN:NBN:fi:bof-201408071687
Keywords: 330; deflation; disinflation; zero lower bound; broadly defined liquidity; socio-economic development; Stability and Growth Pact; EU enlargement; Finanzpolitik; Geldpolitik; Zinspolitik; Inflation; Deflation; Wechselkurspolitik; Japan; China; EU-Staaten; Wirkungsanalyse